Challenges and prospects of integrating mental health education in Chinese schools - Shang, Yingmei; Wang, Jiao; Zhu, Haifeng (Frontiers in Public Health, 2025)
China has long been committed to promoting students’ mental well-being by integrating mental health education (MHE) across primary, secondary, and higher education. This paper offers a comprehensive analysis of how MHE is integrated in Chinese schools. It first examines the current state of integration through a review of policy and relevant literature. It then explores the key challenges across four dimensions: institutional mechanisms, educational practices, targeted interventions, and teacher workforce development. Finally, the paper discusses future directions for advancing MHE in Chinese schools, including updating educational philosophies, strengthening institutional frameworks, building holistic student support systems, and enhancing teacher training, ultimately aiming to promote the high-quality development of MHE in China.